Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5194/bg-9-1465-2012
|View full text |Cite
|
Sign up to set email alerts
|

Increasing iron concentrations in surface waters – a factor behind brownification?

Abstract: Abstract. Browning of inland waters has been noted over large parts of the Northern hemisphere and is a phenomenon with both ecological and societal consequences. The increase in water color is generally ascribed to increasing concentrations of dissolved organic matter of terrestrial origin. However, oftentimes the increase in water color is larger than that of organic matter, implying that changes in the concentration of organic matter alone cannot explain the enhanced water color. Water color is known to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 41 publications
(37 reference statements)
10
189
2
1
Order By: Relevance
“…In many studies on DOC, there is little information available for iron in the discharge. While Kritzberg and Ekström (2012) did observe parallel increases of iron and DOC, they hypothesised that DOC and iron do not necessarily have identical mobilisation processes, as the ratios of iron and DOC varied among catchments. Interestingly, in the catchment under study here, iron to DOC ratios did not change significantly since 1987 (not shown), indicating a parallel dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies on DOC, there is little information available for iron in the discharge. While Kritzberg and Ekström (2012) did observe parallel increases of iron and DOC, they hypothesised that DOC and iron do not necessarily have identical mobilisation processes, as the ratios of iron and DOC varied among catchments. Interestingly, in the catchment under study here, iron to DOC ratios did not change significantly since 1987 (not shown), indicating a parallel dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…While the effect of acid and/or sulfate deposition on catchment DOC export has been demonstrated for many sites and may be responsible for a large part of the observed long-term trends (e.g., reviewed in Clark et al, 2010), the process based understanding from this study adds another potential factor to cause increased DOC exports from catchments. Due to the tight coupling of DOC and iron dynamics and due to the high release of DOC under reducing conditions in wetlands (Zak and Gelbrecht, 2007;Grybos et al, 2009), an increase in iron reducing activity or an increase in reducing conditions and associated increases in pH causing higher DOC mobility and higher microbial activity in general would also explain rising DOC and iron concentrations in catchment exports in a long-term perspective (Kritzberg and Ekström, 2012). Higher microbial activity and higher iron reduction could e.g., be caused by increased temperatures due to climate change (e.g., temperature relationships reported in Winterdahl et al, 2011;Köhler et al, 2008), as depicted for the site under study here in Fig.…”
Section: Pore Water Biogeochemistry and Associated Doc Dynamicsmentioning
confidence: 99%
“…strong correlation with features of covariation between fluxes of TOC and Total Iron (R = 0.91) demonstrating similar sources of both substances (Kritzberg and Ekström, 2012). Meanwhile, in the Lielupe basin the correlation is much less pronounced (R = 0.32), indicating difference of sources.…”
Section: Resultsmentioning
confidence: 89%
“…Although it has been difficult to find out a single factor causing brownification, there is an implicit consensus that the direct factor causing this process is the increased concentrations of terrestrially derived organic matter (OM) in the water (Kritzberg and Ekström, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation